2017
DOI: 10.1111/odi.12707
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human polyomaviruses JC and BK in liver pretransplant patients

Abstract: Cirrhotic patients on the liver transplant waiting list did not show higher prevalence of BKPyV and JCPyV compared to normoreactive controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…When oral fluids are used in screening assays to detect polyomaviruses, the results are highly positive and are especially indicated for patients who are unable to urinate. This positivity in oral fluids occurs even when the patient has negative viremia, which indicates that saliva can be a means for early detection of BKPyV 2 , 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When oral fluids are used in screening assays to detect polyomaviruses, the results are highly positive and are especially indicated for patients who are unable to urinate. This positivity in oral fluids occurs even when the patient has negative viremia, which indicates that saliva can be a means for early detection of BKPyV 2 , 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 46.8% of the participants excreted the virus in their oral fluids, which is a lower percentage than that observed in literature. Diseases related to BKPyV may be associated with a specific immune deficiency as a result of the use of immunosuppressive drugs 3 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing evidence has suggested that there is a connection between human polyomaviruses and the oral compartment [1,[24][25][26][27][28], meaning that saliva can be used as an additional biological fluid to assess the polyomavirus status. Therefore, saliva has gained an increased interest as a non-invasive screening approach to facilitate detection of new cases and monitor previously known cases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Parece que é exatamente isso que vem acontecendo nos últimos anos. Notase que existe uma atenção crescente para a saúde bucal do paciente cirrótico em fila de transplante (Lins et al, 2011;Silva Santos et al, 2012;Helenius-Hietala et al, 2012;Helenius-Hietala et al, 2013;Helenius-Hietala et al, 2014;Olczak-Kowalczyk et al, 2014;Aberg et al, 2014;Grønkjaer, 2015;Grønkjaer;Vilstrup, 2015;Han et al, 2016;Figueiredo et al, 2017;Di Profio et al, 2017;Lins et al, 2017). (Yi et al, 2017).…”
Section: Critérios De Exclusãounclassified